Identifikasi Cedera Atlet Olahraga Tinju Amatir Jawa Tengah Periode Tahun 2020 - KHASANAH, KHIKMAHTUL KHASANAH (Unnes Journal of Sport Sciences, 2021)
Khikmahtul Khasanah. 2021. NIM 6301416032. Identification of Sport Injury Amateur Boxing Athlete in Central Java for the Period of 2020. Description of the Department of Sport Science, Faculty of Sport Science, UNNES, Supervisor Arif Setiawan, S.Pd, M.Pd. Keywords: Identification, injury, Central Java boxing athletes. This study aims to determine the types and injuries seen by athletes in the sport of boxing in Central Java. So that the results obtained can be made new for athletes to prioritize prevention. This research is descriptive research. The method used is a survey method with data techniques using a questionnaire. The research population used in this study were Central Java boxing athletes who were still active and cared for by 50 athletes. The results showed that the identification of injuries that occurred in boxing was head and face injuries with 43% wrist injuries 30%, shoulder injuries 30%, knee injuries 13%, knuckles injuries 23%, angkle pad injuries (ankle) 17%. And the factors causing injury during training or competition 37%. The incidence of injury was 33%. 73% security tool.